Influência do método de síntese no processo de pilarização com titânio de uma esmectita da região amazônica - GUERRA, Denis de Jesus Lima (2012)
Smectite clays of the State of Acre, Brazil, were used for the pillarization process. The natural and pillarized matrices were characterized by X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), thermal analysis, scanning electron microscopy, energy dispersive spectroscopy and textural analysis. The titanium pillarized solutions Ti(OC2H5)4 and TiCl4 were analyzed by FTIR. The intercalation ion was obtained by reacting Ti(OC2H5)4 with HCl (HCl/Ti ~ 1) and TiCl4 with ethanol (Ti/clay ~ 25 mmol Ti/g). The notronite intercalation was carried out using two methods: with dropwise hydrochloric acid in titanium ethoxide solution, and using titanium tetrachloride, kept under vigorous stirring at 25 °C for 3 h and calcination at 450 °C and 600 °C. The X-ray diffraction results of the pillarization process show an increase (15.30 Å to 18.76 Å) in the basal spacing of the natural clay and in the specific surface area (44.37 m2/g to 188.72 m2/g) The thermal stability of the natural clay was improved by the pillarization procedure.